A Patent Review and Current Status of Ultra-thin Vapour Chamber - Dong, Boxiong; Xie, Baocheng (Recent Patents on Engineering, 2025)
BackgroundWith the advent and rapid development of 5G technology, many electronic products have been developed in the miniaturized direction. However, excessive operating temperature generated by these electronic products in a small space results in serious runaway problems, such as battery failure and dead equipment. To solve the heat dissipation problem of small electronic products, ultra-thin vapour chambers are widely used in the heat dissipation field of these electronic products due to the characteristic of rapid heat conduction and thermal expansion. Therefore, optimizing the performance of ultra-thin vapour chambers is critical. Over the years, optimizing the performance of ultra-thin vapour chambers has piqued the industry's interest.ObjectiveThis study aimed at exploring the structural features, optimization method, and development status of the ultra-thin vapour chambers.MethodsThis patent study reviews various representative patents related to ultra-thin vapour chambers and discusses the problems existing in the process of achieving ultra-thinning to provide a reference for designers of ultra-thin vapour chambers in the future.ResultsThrough the investigation of a large number of patents on ultra-thin vapour chamber, some existing problems are summarized and analyzed. Finally, the future trend of ultra-thin vapour chambers is discussed.ConclusionThe optimization of ultra-thin vapour chambers benefits the heat dissipation of small electronic products and improves product safety. More related patents will be published in the future.
Keywords: etching